Strategic use of digital promotion strategies among female emigrant entrepreneurs in UAE. Issue 6 (29th November 2018) - Jose, Saju
Abstract : Purpose: The purpose of this paper is to examine the strategic use of social media and chat applications of women entrepreneurs to promote their businesses. Design/methodology/approach: Because of the nature of the study and dearth of sufficient data in the Middle Eastern society on the women entrepreneurship, this study employed a qualitative research methodology. The research comprised of 20 in-depth interviews with immigrant women entrepreneurs in the United Arab Emirates. They were identified through personal contacts and referrals. Findings: All the expatriate women interviewed are using social media and chat applications to promote their business. Facebook is used for brand creation and WhatsApp is used as a direct marketing tool to evoke purchase response. Though traditional promotional tools are far from redundant, their role is more supplementary. The increasing trend is a combination of traditional tools and digital tools. Digital tools seem to have an upper hand in their business promotions. Research limitations/implications: This study is limited to SME sector in one industry and in one country. The qualitative nature of this study could affect the generalizability of the results. A more extensive study is needed and future research should be more diverse including widening the selection of respondents, industries and countries. Originality/value: This study is a novel attempt to gauge an in-depth understanding of modern communication tools. It looks specifically at the integrative strategies pursued by the immigrant women entrepreneurs using Facebook and WhatsApp.